Online Damping Strategy for Controlling Heaving Wave Energy Converters Using Three-Phase Bridge Boost Rectifier - Mohammed Jama; Addy Wahyudie (IEEE Access, 2017)
One of the main research questions in the field of wave energy technologies concerns the development of an efficient control strategy that can enhance the economic competitiveness of these technologies. Numerous control strategies have been proposed in the past three decades of which only a few are deemed practical. This paper proposes a novel online damping control strategy that is based on the development of an explicit relation for controlling the damping force of a permanent magnet linear generator (PMLG) in real time. The strategy controls the duty cycle of a single-switch three-phase boost rectifier connected at the output terminals of the PMLG. Simulations were conducted to assess the performance of the wave energy converter after applying the proposed strategy under different operating conditions. The results showed satisfactory performances for different sea-state and electrical-loading conditions.